Does pleurotomy for internal mammary artery harvest increase postoperative complications? A comparative study of internal mammary artery harvest with and without pleurotomy - Palanki, Surya Satya Gopal; Kummari, Madhusudan; Dontineni, Praveen; Malempati, Amaresh Rao; Bomma, Kaladhar (International Journal of Research in Medical Sciences, 2021)
Background: To assess and compare the postoperative complications in patients who are undergoing Left Internal Mammary artery harvesting for coronary artery bypass grafting surgery with pleurotomy and without pleurotomy. Methods: The study was conducted on the patients admitted in a single unit of department of cardiothoracic surgery,NIMS, Hyderabad during the period of July 2017 to December2017. The study was a randomized open labelled controlled trial of two interventions.A total of 90 patients undergoing Coronary artery bypass surgery were enrolled in the study,with 60 among them having their Internal mammary harvesting done with pleurotomy and 30 undergoing the same without pleurotomy. Results: In the non pleurotomy group, 16 (53.33%) were male and 14 (46.66%) were female.In the pleurotmy group males and females were 41 (68.33%) and 19 (31.66%) respectively.There was no statistical significance between both the groups with respect to posteroperative bleeding, icu stay, reexploration rate,duration of ventilation,PaO2 and PCo2 values or wound infection rates. The only difference between both the groups which showed statistical significance(0.051) was the occurence of pleural effusion on POD 5 .In the closed pleurotomy group only 2(6.66%) patients had pleural effusion upto POD5, whereas in the open pleurotomy group 14 (23.33%) patients had pleural effusion persisting till POD5. Conclusions: There is a higher incidence of Pleural effusion in the pleurotomy group although this did not translate into higher postop pain score,ICU/Hospital stay, wound infection rates.